Edukasi Pengetahuan Orang Tua Tentang Diabetes Melitus (DM) dan Screening Risiko DM pada Anak Usia Sekolah di SD Negeri 1 Dukuhwaluh - Nudin, Jauhar; Wirakhmi, Ikit Netra; Khasanah , Suci (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The rising prevalence of Diabetes Mellitus (DM) among children highlights the need for early intervention, particularly through parental education and lifestyle supervision. This study aimed to improve parents’ knowledge about DM and conduct risk screening for school-aged children at SD Negeri 1 Dukuhwaluh. The program was carried out through health education sessions for 70 parents using pre-test and post-test assessments, and health screening for students in grades 4 to 6, involving random blood glucose tests, BMI measurement, and identification of classic DM symptoms. The results showed a significant increase in parental knowledge, with those in the "Fair" category dropping from 37.21% to 9.31%, and the emergence of the "Excellent" category reaching 18.61%. Children's screening results also showed a reduction in those at "Low Risk" from 15.38% to 6.15%, while the "No Risk" category increased from 84.62% to 93.85%. These findings indicate that integrated education and screening approaches can effectively support the prevention of DM in school-aged children. The implications suggest that ongoing collaboration between schools and families is essential for effective health promotion programs.